Aggregation induced emission of diketopyrrolopyrrole (DPP) derivatives for highly fluorescent red films. Issue 5 (18th January 2019) - Hwang, Tae Gyu; Kim, Jeong Yun; Namgoong, Jin Woong; Lee, Jae Moon; Yuk, Sim Bum; Kim, Se Hun; Kim, Jae Pil
Abstract : Triphenylamine moieties substituted diketopyrrolopyrrole derivatives showed highly emissive characteristics in solid film state by aggregation induced emission. Abstract : A large number of diketopyrrolopyrrole (DPP) compounds showing aggregation induced emission (AIE) have been reported in the past few years. However, although DPP compounds exhibited AIE and excellent luminescence properties, their luminescence properties in solid or film states were not much focused on. Here we synthesized and characterized a series of DPP compounds with triphenylamine (TPA) moieties to investigate the AIE properties in the solid film state depending on the functional groups (TPA, BTPA, and MTPA) attached to the TPA moieties.T2 andD2 thin films showed excellent fluorescence quantum yields of 31% and 26%, respectively, compared to anM2 thin film (9%). The restriction of an intramolecular rotation process could inhibit the aggregation induced quenching process and play a key role in achieving highly fluorescent molecules in the solid state.